Drought stress during maize flowering may cause kernel abortion by inhibition of plasma membrane H + -ATPase activity - Hütsch, Birgit W.; Faust, Franziska; Jung, Stephan; Schubert, Sven; Justus Liebig University Giessen (My University, 2024)
Background: Drought stress during flowering of maize (Zea mays L.) frequently results in decreased kernel setting, leading to grain yield depressions. Plasma membrane (PM) H+-ATPase was identified as a key enzyme responsible for supply of assimilates to the developing maize kernels shortly after pollination. The activity of this enzyme was strongly inhibited under salt stress, pointing to an involvement in kernel abortion. Aims: This study aimed to determine whether also drought stress causes inhibition of PM H+-ATPase in developing maize kernels shortly after pollination, leading to diminished hexose uptake and finally kernel abortion. The key questions are as follows: What are the limiting factors for grain yield production of maize plants facing drought? Are physiologically relevant parameters, quantified at flowering, reflected by yield determinants at maturity? Methods: Maize plants were cultivated using the container technique, and drought stress was imposed during 3 weeks bracketing flowering compared to well-watered conditions throughout the entire growth period. The developing kernels were harvested 2 days after pollination, and PM vesicles were isolated and purified using two-phase partitioning. Results: Water deficit caused a significant decrease in grain yield at maturity (−35%), which was determined by a reduced kernel number (−42%). Source limitation in the developing kernels under stress could be excluded. Acid invertase activity was unaffected by water deficit. Hexose availability was also no limiting factor for kernel setting and development. However, Vmax of in vitro hydrolytic activity of PM H+-ATPase was significantly decreased in the developing maize kernels under drought stress and the maximal pH gradient at the PM was also significantly reduced. The observed inhibiting effects on PM H+-ATPase were mainly of quantitative nature, as a lower number of proton pumps was present in the kernel PM. Qualitative changes of the enzyme (activation energy Ea, Michaelis constant Km) due to drought were not observed. Conclusions: The lower pH gradient probably decreased the proton-driven transport of hexoses by carriers into the cytosol of the kernel cells, leading to kernel starvation and eventually contributing to kernel abortion.